Root and Canal Morphology of Maxillary Teeth in an Iranian Subpopulation Residing in Western Iran Using Cone-beam Computed Tomography - Nikkerdar, Nafiseh; Asnaashari, Mohammad; Karimi, Atena; Araghi, Solmaz; Seifitabar, Shahin; Golshah, Amin (Iranian Endodontic Journal, 2020)
Introduction: Accurate information regarding the morphology of roots and canals is a prerequisite for successful endodontic treatment. This study aimed to assess the number of roots and canals and canal type of maxillary teeth according to the Vertucci’s classification in an Iranian subpopulation residing in Western Iran using cone-beam computed tomography (CBCT). Methods and Materials: In this cross-sectional study, a total of 1750 teeth were evaluated on CBCT scans taken for purposes other than this study. For each tooth, 250 axial, sagittal and coronal sections with 1 mm slice thickness were evaluated using NNT Viewer software. The number of roots and canals and canal type according to the Vertucci’s classification were determined and reported. Data were analyzed using descriptive and analytical statistics via Fisher’s exact test and Chi square test. All data analyses were performed using SPSS version 18. Results: All of the maxillary anterior teeth were single-rooted, and Vertucci’s type I was the most common canal type. Maxillary premolars were mostly single-rooted and Vertucci’s type I was the most common type except for the first maxillary premolars, in which type V had the highest frequency. Maxillary molars mostly had three roots and two canals in the mesiobuccal root and one canal in the distobuccal and palatal roots. Conclusion: Although the number of roots in this cross-sectional study was similar to the findings of previous studies, canal type was significantly different from the results of previous studies. The result of this study can help clinicians in efficient root canal treatment of teeth. Keywords: Cone-beam Computed Tomography; Maxilla; Root Canal Morphology